2017
DOI: 10.12968/bjhc.2017.23.6.262
|View full text |Cite
|
Sign up to set email alerts
|

The reforming appeal of distributed leadership

Abstract: With a systematic literature review, this article examines the significance of distributed leadership in health care, assessing the extent to which it reflects a consistent set of values, meanings, practices and outcomes. It identifies key mediating factors and their importance in enabling or constraining distributive leadership processes. The findings indicate that clinicians without formal leadership titles are inspiring change and driving improvements, although countervailing pressures are limiting this in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…The challenge of how to integrate research in healthcare is arguably not amenable to hierarchical leadership. Distributed leadership offers a means of harnessing insights from multiple stakeholders and improving the quality of decision-making [25]. Study findings accord with current literature on leadership and several participants identified that distributed and collective leadership need to be embedded and evaluated in RTCs.…”
Section: Discussionsupporting
confidence: 75%
“…The challenge of how to integrate research in healthcare is arguably not amenable to hierarchical leadership. Distributed leadership offers a means of harnessing insights from multiple stakeholders and improving the quality of decision-making [25]. Study findings accord with current literature on leadership and several participants identified that distributed and collective leadership need to be embedded and evaluated in RTCs.…”
Section: Discussionsupporting
confidence: 75%
“…The challenge of how to integrate research in healthcare is arguably not amenable to hierarchical leadership. Distributed leadership offers a means of harnessing insights from multiple stakeholders and improving the quality of decision making (26). Study ndings accord with current literature on leadership and several participants identi ed that distributed and collective leadership need to be embedded and evaluated in RTCs.…”
Section: Discussionsupporting
confidence: 70%
“…The challenge of how to integrate research in healthcare is arguably not amenable to hierarchical leadership. Distributed leadership offers a means of harnessing insights from multiple stakeholders and improving the quality of decision making (26). Accordingly, several participants identified that distributed leadership now needs to be embedded in RTCs and evaluated.…”
Section: Discussionmentioning
confidence: 99%